Microbial evaluation of selected produce pre- and post-pack-house and at the formal retail point-of-sale - Kavela, Efaishe Tweuhanga Angaleni (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScFoodSc)--Stellenbosch University, 2020.